1989
DOI: 10.1148/radiology.171.3.2717731
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis: correlation of pulmonary parenchymal pattern at CT with results of pulmonary function tests.

Abstract: The appearances of the lungs on radiographs and computed tomographic (CT) scans were correlated with degree of uptake on gallium scans and results of pulmonary function tests (PFTs) in 27 patients with sarcoidosis. CT scans were evaluated both qualitatively and quantitatively. Patients were divided into five categories on the basis of the pattern of abnormality at CT: 1 = normal (n = 4); 2 = segmental air-space disease (n = 4); 3 = spherical (alveolar) masslike opacities (n = 4); 4 = multiple, discrete, small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(64 citation statements)
references
References 0 publications
0
60
3
Order By: Relevance
“…Many research groups have investigated CT as a non invasive examination in distinguishing patients with active disease and potentially reversible lesionsfrom those with irreversible fibrotic disease [26][27][28]. Results of these studies though seem to be inconsistent [19,16,[28][29][30]. However, two studies Oberstein et al [12] and Leung et al [19] reported solid evidence of HRCT correlation with disease activity markers such as BAL total cell and lymphocyte counts, IL-2R, CD4/CD8 ratio, IL-2R and HLA-DR. Their results showed that specific HRCT abnormalities including bronchovascular bundle thickening and intraparenchymal nodules correlate well with the above mentioned disease activity markers [12].…”
Section: Discussionmentioning
confidence: 99%
“…Many research groups have investigated CT as a non invasive examination in distinguishing patients with active disease and potentially reversible lesionsfrom those with irreversible fibrotic disease [26][27][28]. Results of these studies though seem to be inconsistent [19,16,[28][29][30]. However, two studies Oberstein et al [12] and Leung et al [19] reported solid evidence of HRCT correlation with disease activity markers such as BAL total cell and lymphocyte counts, IL-2R, CD4/CD8 ratio, IL-2R and HLA-DR. Their results showed that specific HRCT abnormalities including bronchovascular bundle thickening and intraparenchymal nodules correlate well with the above mentioned disease activity markers [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although scoring methods are different there are a few studies describing the scoring of CT findings to compare our results with [5][6][7][8][9]14]. In 2003, Drent et al described inter-rater agreement using the scoring system proposed by Oberstein [6,25].…”
Section: Ct Scoring Systemsmentioning
confidence: 99%
“…There appears to be good reported agreement between raters in scoring a limited number of abnormal CT findings in sarcoidosis with kappa values ranging from 0.81 to 0.89. These results are based on studies focussing on correlations between abnormal CT findings and pulmonary function impairment; however, the number of raters as well as the number of abnormal CT findings studied has been limited [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…PFTs and HRCT are also important for the followup of the progression and activation of the disease [3][4][5]. In addition to restrictive respiratory dysfunction, obstructive dysfunction can also be observed in sarcoidosis.…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node involvement is present in stages I and II; lung parenchyma involvement of the disease is present in all stages, except stages 0 and I of the disease [6]. There are some studies in the literature showing a relationship between the presence of radiologic findings and PFTs, however, there is no previous study, according to our knowledge, investigating separately the parenchymal involvement and individual lymph node involvement effect on PFTs [2,5]. In this study, we aimed to investigate the effect of lymphadenopathy (LAP) alone or after controlling pulmonary parenchymal involvement on PFTs in the context of sarcoidosis.…”
Section: Introductionmentioning
confidence: 99%